A Comparison of the Surgical Outcomes Among Patients With HBV-positive, HCV-positive, and Non-B Non-C Hepatocellular Carcinoma: A Nationwide Study of 11, 950 Patients. Issue 3 (March 2015) - Utsunomiya, Tohru; Shimada, Mitsuo; Kudo, Masatoshi; Ichida, Takafumi; Matsui, Osamu; Izumi, Namiki; Matsuyama, Yutaka; Sakamoto, Michiie; Nakashima, Osamu; Ku, Yonson; Takayama, Tadatoshi; Kokudo, Norihiro
Abstract : Objective: To compare the prognostic factors and outcomes after hepatic resection among patients with hepatitis B virus (HBV)-positive, hepatitis C virus (HCV)-positive, and negative for hepatitis B surface antigen and hepatitis C antibody, so-called "NBNC"-hepatocellular carcinoma (HCC) using the data from a nationwide survey. Background: The incidence of NBNC-HCC is rapidly increasing in Japan. Methods: A total of 11, 950 patients with HBV-HCC (n = 2194), HCV-HCC (n = 7018), or NBNC-HCC (n = 2738) who underwent a curative hepatic resection were enrolled in this study. The clinicopathological features were compared among the groups. The significant prognostic variables determined by univariate analysis were subjected to a multivariate analysis using a Cox proportional hazard regression model. Results: Liver function in the HCV-HCC group was significantly worse than that in the HBV-HCC and NBNC-HCC groups. The NBNC-HCC group had significantly more advanced HCC than the HCV-HCC group. The 5-year overall survival rates after hepatectomy in the HBV-HCC, HCV-HCC, and NBNC-HCC groups were 65%, 59%, and 68%, respectively. The 5-year recurrence-free survival (RFS) rates in these 3 groups were 41%, 31%, and 47%, respectively. Stratifying the RFS rates according to the TNM stage showed that the NBNC-HCC group had a significantly better prognosis than the HBV-HCC group in stages II, III, and IVA, and a significantly better prognosis than the HCV-HCC group in stages I and II. Multivariate analysis revealed a significantly better RFS rate in the NBNC-HCC group. Conclusions: The findings of this nationwide survey indicated that patients with NBNC-HCC had a significantly lower risk of HCC recurrence than those with HBV-HCC and HCV-HCC. Abstract : Supplemental Digital Content is Available in the Text.Clinicopathological features after hepatectomy among the 11, 950 patients with hepatitis B virus-hepatocellular carcinoma (HBV-HCC), hepatitis C virus (HCV)-HCC, and non-B non-C (NBNC)-HCC were compared. Liver function in HCV-HCC group was significantly worse, whereas NBNC-HCC group had significantly more advanced HCC. The multivariate analysis revealed that NBNC-HCC group had a significantly better recurrence-free survival rate than HBV-HCC and HCV-HCC groups.